Academic workshops held by the PET Dentistry group: An experience report (Research, Society and Development, 2021)
The Tutorial Education Program (PET) of the Dentistry course at the State University of Maringá (UEM), prepares academic workshops with multidisciplinary content, seeking to enrich the undergraduate education. Thus, it provides a form of teaching, which involves all participants in tasks and activities, favoring the space for discussion and exchange of knowledge. Therefore, the aim of the present paper is to report the experience of the academic workshop of the PET Dentistry UEM group. The workshops are organized by the members of the PET group themselves, in which lectures / workshops are held on some topics previously decided in an administrative meeting with the members and tutor of the group. Four editions have already been held and in each of them two themes were addressed, setting aside a day for each theme. Among them are: formatting panels, PowerPoint, summaries, oratory, making and developing spreadsheets, how to better manage time, basic rules of the camera for the clinician and basics of photoshop, basic communication in pounds and organization of the lattes curriculum. Workshops were given to previous registered undergraduates that took the necessary materials to do the tasks. At the end of the events, evaluations were distributed to be completed by the participants, providing positive feedback to the group. In view of the various benefits that the academic workshop brings to undergraduate courses, such as stimulating knowledge, the work of the PET group in training a broad academic background is of paramount importance.